Laser Micro Welding of Dissimilar Metals - Schmidt, Michael; Jahrsdörfer, Bernd; Mys, I. (Proceedings of the 23rd International Congress on Applications of Laser & Electro-Optics ICALEO, 2004)
Joining of dissimilar metals is a challenging task in many fields of application. Often liquid phase joining produces material properties in or nearby the joint that do not fit the requirements for the whole workpiece. The need for those joints occurs in mechanical as well as in electro - mechanical interconnects. Copper is the material mostly used in electronic applications due to its high electrical and thermal conductivity. On the other hand aluminum offers technical and economical advantages with respect to cost and component weight, still providing thermal and electrical properties acceptable for numerous applications. Especially for high volume products, the best solution often is a combination of both materials. With respect to miniaturization of those joints laser micro welding is a promising technique. Unfortunately, the metallurgical incompatibility of copper and aluminum results in the formation of brittle intermetallic phases and segregations, thus generating an unacceptable quality of the joints. Investigations on laser micro welding of copper and aluminum will be presented for applications in high power and automotive electronics. In order to eliminate the formation of brittle intermetallic phases, the addition of a filler material in form of a foil will be shown. The addition of pure metal such as silver significantly reduces the occurrence of brittle phases in the joining area and therefore leads to an increasing welding quality especially with respect to static and dynamic mechanical properties. "Laser Droplet Welding" is an innovative technique also useful for producing material conclusive connections between dissimilar metals. This paper provides a closer look at this welding process for stainless steel and titanium. An analysis of the microstructure in the welding area and hardness tests allow a deeper insight into metallurgical changes during the process by issuing qualitative and even quantitative information.
LFT Import::2019-08-05 (1076)